Characterizing the microbiome recruited by the endangered plant Firmiana danxiaensis in phosphorus-deficient acidic soil - Li, Jiayu; Tang, Guangda; Liu, Hongwei; Luo, Xiaoying; Wang, Juntao (Frontiers in Microbiology, 2025)
Phosphorus (P)-deficient soils serve as crucial habitats for endangered plant species. Microbiomes play pivotal roles in soil element cycling and in determining a plant’s adaptability to the environment. However, the relationship between the endangered plant, microbiome, and soil stoichiometric traits, and how it affects plant adaption to P-deficient habitats remain largely unexplored. In this study, we investigated the microbiome (bacteria and fungi) in the rhizosphere of Firmiana danxiaensis, an endangered plant species growing exclusively in P-deficient acidic soils on Mt. Danxia, South China; the non-endangered coexisting tree species Pinus massoniana was used as a reference. Our results showed that soil traits in the rhizosphere of F. danxiaensis differed significantly from that of P. massoniana, including higher soil pH, lower C:N, and higher N:P. The rhizosphere of F. danxiaensis harbors higher microbial diversity and different microbial communities from P. massoniana. Using the machine learning approach, we characterized 76 bacterial and 20 fungal phylotypes dominated in F. danxiaensis rhizosphere, most of which had strong impacts on microbial ecological network structure (they accounted for only 0.33% node numbers but linked 21.2% of the nodes in the network); specifically, Udaeobacter spp., a highly abundant (constituting 4.07% of the total bacterial community) member of Verrucomicrobiota exclusively accumulated in the rhizosphere of F. danxiaensis but not P. massoniana, demonstrated a pronounced ecological prefers toward F. danxiaensis rhizosphere habitat (high pH, low C:N and high N:P) and potential antagonistic indication. In contrast, P. massoniana rhizosphere harbored more Subgroup2 of Acidobacteria and Gammaproteobacterial N-fixer. Taken together, this study provided novel evidence that endangered plants recruited a unique microbiome characterized by Udaeobacter spp. favoring high N habitat. It contributes not only to our understanding of microbiome recruitment by plants in P-deficient acidic soils, but also underscores the importance of microbiome in the conservation and population restoration of endangered plants.